Soil mechanics fundamentals and applications - Ishibashi, Isao; Hazarika, Hemanta (CRC Press/Taylor & Francis, 2015)
This latest edition includes all the fundamental concepts of soil mechanics, as well as an introduction to foundation engineering, including coverage of site exploration, shallow and deep foundation design, and slope stability. It presents the material in a systematic, step-by-step manner, and contains numerous problems, examples, and solutions.